PEMANFAATAN E-MODUL INTERAKTIF PADA MATERI TEKS FABEL: UTILIZATION OF INTERACTIVE E-MODULES IN FABLE TEXT MATERIALS - Selvia Nur Qomarina; Didah Nurhamidah (Sasando, 2023)
This study aims to describe the use of interactive e-modules to assist in learning Fable Texts. Interactive e-module applications are android-based applications that teach about PUEBI by presenting material summaries, learning videos, material slides, and practice questions. This research method uses a descriptive qualitative method. The questionnaire for the research sample was 24 grade 7 students at SMP IP Yakin Jakarta. The results of the study showed that the use of interactive e-module media for learning, especially in fable text material, received a good response, seen from the positive responses of students in filling out the questionnaire. The interactive e-module application is considered capable of being an innovative learning medium for teaching Fable Texts in a more attractive and less boring way.